The Effect of Teaching Games for Understanding on Volleyball Playing Skills of Junior High School Students - Mochammad Ikhsanul Al Raffi; Ega Trisna Rahayu; Fauzi Miftakh (Ilmu Olahraga, 2026)
This study aims to determine the significant effect of the Teaching Games for Understanding (TGfU) learning model on improving volleyball playing skills of eighth-grade students at State Junior High School 1 (SMPN 1) Majalaya, Karawang Regency. The research method employed was quantitative experimental design using The Randomized Control Group Pretest-Posttest design. The study involved 68 students divided into two groups: an experimental group and a control group. The learning intervention was implemented over 8 meetings. Data were collected using the Game Performance Assessment Instrument (GPAI) and analyzed using descriptive statistics, normality tests, homogeneity tests, paired samples t-test, independent samples t-test, and N-Gain Score calculations with a significance level of α = 0.05 using SPSS version 25. The research results revealed a very significant increase in the experimental group, with the mean pretest score of 6.01 increasing to a posttest score of 8.11, while the control group experienced only minimal improvement from 5.84 to 5.86. The independent samples t-test demonstrated a very significant difference between the mean posttest scores of the experimental and control groups (p=0.000) with a mean difference of 2.25 points. The N-Gain Score value in the experimental group was in the high category (0.72), while the control group was in the low category (0.05). In conclusion, the TGfU learning model has been proven empirically to be more effective and significant in improving volleyball playing skills compared to the Direct Instruction learning model in junior high school students.